2018
DOI: 10.1002/zoo.21391
|View full text |Cite
|
Sign up to set email alerts
|

A work‐for‐food enrichment program increases exploration and decreases stereotypies in four species of bears

Abstract: Zoo-housed bears are prone to exhibiting stereotypic behaviors, generally considered indicators of negative welfare. We explored the effects of a variable-time feeding enrichment schedule on behavioral indicators of welfare in four bear species at Cleveland Metroparks Zoo. We distributed the diets of eight bears in one of five enrichment items, for two consecutive days each, and monitored behavior throughout the day. In Experiment 1, we compared variable-time to fixed-time presentation of enrichment over two, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Nevertheless, for wolf 2 and wolf 4 exploration also increased when food was hidden around the enclosure. In accordance with previous studies [18,19,20,46,47], this finding suggests that the relationship between feeding enrichment and exploratory behaviour is more linear and less affected by individual variables than the other behavioural indicators we assessed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, for wolf 2 and wolf 4 exploration also increased when food was hidden around the enclosure. In accordance with previous studies [18,19,20,46,47], this finding suggests that the relationship between feeding enrichment and exploratory behaviour is more linear and less affected by individual variables than the other behavioural indicators we assessed.…”
Section: Discussionsupporting
confidence: 93%
“…Several behavioural indicators of welfare have been used to assess the effects of feeding enrichment programs. In carnivores, feeding enrichment has been shown to decrease stereotypies [14,17], improve behavioural diversity [18,19], increase exploration [20] and activity levels [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although, as noted above, mate-seeking behavior may be causally related to the May through July occurrence of stereotypies, the times at which these stereotypies occurred still appeared entrained to the feeding schedules. Past research has shown similar patterns for stereotypic pacing in zoo bears, with pacing occurring in anticipation of food events and reduced as a result of providing multiple feeding opportunities [26,37,[59][60][61].…”
Section: Daily Activitymentioning
confidence: 80%
“…While the relationship between stereotypies, general activity, and feeding schedules for zoo-housed animals is less clear, it appears that many aspects of feeding schedules and feeding enrichment directly entrain the circadian rhythms of those captive animals. Aside from the use of multiple feedings and environmental enrichment previously discussed, simply changing the predictability/variability of feeding events is effective at increasing general activity and reducing abnormal behaviors, such as stereotypies [60,61]. In addition, grizzlies will choose to engage in foraging-related activity over freely distributed feeding opportunities (i.e., contrafreeloading) [62].…”
Section: Daily Activitymentioning
confidence: 99%
“…Applied research should be used to inform these policy documents. There is a growing body of published work on applied animal welfare science in the zoo sector which explores the welfare consequences of various factors such as enrichment provision [ 14 , 15 , 16 ], enclosure design [ 17 , 18 , 19 ], social groupings [ 20 ], and human impacts [ 21 , 22 , 23 , 24 ]. This type of research is valuable in informing housing and husbandry standards for zoos, and clearly further study is needed to address the wide taxonomic spread of species housed in these settings.…”
Section: Introductionmentioning
confidence: 99%